2020
DOI: 10.3389/fmars.2020.00091
|View full text |Cite
|
Sign up to set email alerts
|

Positive Ecological Interactions and the Success of Seagrass Restoration

Abstract: Seagrasses provide multiple ecosystem services including nursery habitat, improved water quality, coastal protection, and carbon sequestration. However, seagrasses are in crisis as global coverage is declining at an accelerating rate. With increased focus on ecological restoration as a conservation strategy, methods that enhance restoration success need to be explored. Decades of work in coastal plant ecosystems, including seagrasses, has shown that positive species relationships and feedbacks are critical for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
87
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 126 publications
(138 reference statements)
3
87
0
Order By: Relevance
“…Here, we show that by deploying transplants inside establishment structures, our salt marsh transplant size was nine times smaller compared to the earlier applied clumped transplant design 16 , greatly reducing the need for donor material and avoiding potential damage to donor sites or demands on nurseries to cultivate transplants. As clumping has also been previously found to benefit seagrass transplants 51 , and a review and separate global analysis showed that small-scale facilitations and large-scale approaches will generally benefit seagrass restoration success 17,52 , our finding suggests that the use of establishment structures may be more beneficial for seagrass restoration.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Here, we show that by deploying transplants inside establishment structures, our salt marsh transplant size was nine times smaller compared to the earlier applied clumped transplant design 16 , greatly reducing the need for donor material and avoiding potential damage to donor sites or demands on nurseries to cultivate transplants. As clumping has also been previously found to benefit seagrass transplants 51 , and a review and separate global analysis showed that small-scale facilitations and large-scale approaches will generally benefit seagrass restoration success 17,52 , our finding suggests that the use of establishment structures may be more beneficial for seagrass restoration.…”
Section: Discussionsupporting
confidence: 67%
“…3D-printing may, for example, prove a very useful tool to develop biodegradable prototypes as it opens up virtually infinite design possibilities and allows for fine details at the microscale 56,57 . To enable such optimization, identifying the bottlenecks that hamper establishment of the target species should be the first step 19,52,58 . Next, it should be established whether the target species, or species that mutualistically interact with the target species 59 , possesses emergent traits that mitigate these bottlenecks, after which the establishment structure's design can be improved to more accurately simulate these traits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once settled, survival of individuals to a stage when they in turn can reproduce depends on the presence of conditions necessary for growth, such as food or light, and the absence of negative influences that cause mortality, such as predators, competitors, or physiological stressors (e.g., Doropoulos et al, 2016). Survival and growth can also sometimes be enhanced by the presence of conspecifics, or by symbiotic or mutualistic interactions (Valdez et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, the foundational paradigm in coastal and marine restoration has been that competition limits an organism's regrowth. Accordingly, restoration projects have focused on minimizing negative interactions, while largely ignoring potential positive ones (Silliman et al, 2015;Renzi et al, 2019;Valdez et al, 2020). However, this "foundational" principle stating that negative interactions are paramount in restoration came directly from forestry science without first testing it in marine systems (Halpern et al, 2007).…”
Section: Introductionmentioning
confidence: 99%